RESILIÊNCIA, VALORES HUMANOS E PERCEPÇÃO DE SUPORTE SOCIAL EM PROFISSIONAIS DA SAÚDE - Pieroni, Juliana Martinez (2012)
The current perspective of psychological science, coupled with all aspects of positive psychology and health, allows researching of the resilience phenomenon, turning old questions into new understanding possibilities, and admitting a positive outlook of human beings, rather than looking at its negative aspects, focusing instead on all virtuous aspects, such as resilience, happiness, optimism, altruism, hope, as favorable resources for health maintenance and promotion. The perception of social support protects individuals against destabilization, and human values contribute to human decision-making and choices for conflict resolution. The aim of this research was to determine whether human values and perceptions of social support predict resilience in health care professionals. 127 Brazilians took part on the research, all of them being health professionals, 76% female, mean age of 38 years, and mostly married. The instruments used for data collection were a sociodemographic questionnaire, the Resilience Assessment Scale, the Questionnaire Profiles QPV Values Scale and Perceived Social Support EPSS. Calculations of descriptive statistics, t tests and standard multiple linear regression analysis were made. The results showed that the participants have high levels of resilience, apprehending that they receive more emotional support, move and guide their actions and behaviors for the positive welfare of others. Results of regression analysis revealed that only human values are predictors of resilience. These findings contribute to the understanding of the construct of resilience as a state or process, and therefore, as a dynamic phenomenon that takes into account the context in which the human being is inserted. It also reveals the importance of individual characteristics in explaining this phenomenon. Given the limitations of this study and considering that no empirical study was found prior to this research on the influence of values on human resilience, the results indicate the need for development of further researching to better understand the predictors of resilience. A research agenda is suggested at the end of the conclusions.